Nonviral siRNA delivery systems for pancreatic cancer therapy. Issue 10 (8th July 2021) - Aghamiri, Shahin; Raee, Pourya; Talaei, Sam; Mohammadi‐Yeganeh, Samira; Bayat, Shiva; Rezaee, Delsuz; Ghavidel, Afshin A.; Teymouri, Alireza; Roshanzamiri, Soheil; Farhadi, Shohreh; Ghanbarian, Hossein
Abstract: The serious drawbacks of the conventional treatment of pancreatic ductal adenocarcinoma (PDAC) such as nonspecific toxicity and high resistance to chemo and radiation therapy, have prompted the development and application of countless small interfering RNA (siRNA)‐based therapeutics. Recent advances in drug delivery systems hold great promise for improving siRNA‐based therapeutics and developing a new class of drugs, known as nano‐siRNA drugs. However, many fundamental questions, regarding toxicity, immunostimulation, and poor knowledge of nano‐bio interactions, need to be addressed before clinical translation. In this review, we provide recent achievements in the design and development of various nonviral delivery vehicles for pancreatic cancer therapy. More importantly, codelivery of conventional anticancer drugs with siRNA as a new revolutionary pancreatic cancer combinational therapy is completely discussed. Abstract : Recent advances in drug delivery systems hold great promise for improving siRNA‐based therapeutics and developing a new class of drugs, known as nano‐siRNA drugs. However, many fundamental questions, regarding toxicity, immunostimulation, and poor knowledge of nano‐bio interactions, need to be addressed before clinical translation. In this review, we provide recent achievements in the design and development of various non‐viral delivery vehicles for pancreatic cancer therapy.